Assessment of post-stocking mortality for tiger muskies and strategies to increase survival - Koupal, Keith D., author; Flickinger, Stephen A., advisor; Satterfield, James R., Jr., committee member; Behnke, Robert J., committee member; Bowden, David C., committee member (Colorado State University. Libraries, 1999)
This research was designed to determine major sources of post-stocking mortality for tiger muskies (Esox lucius X E. masquinongy). a stocking strategy to alleviate post-stocking mortality, and an acceptability index to effectively allocate available juvenile tiger muskies. Fish predation appears to have caused post-stocking mortality of 8-49% during 3 years of experimental pond trials, but results were only significant at the 0.05 level in 1 year. However, the consistency of results implicates fish predators as a major contributor to post-stocking mortality of tiger muskies. Bird scarring was observed on a range of 5-17% of surviving tiger muskies during these same experimental pond trials, which suggests that bird predation may also contribute to post-stocking mortality of tiger muskies. Stocking stress, inability to efficiently capture prey, and insufficient condition to survive overwinter were not found to contribute to post-stocking mortality. Providing tiger muskies with predator training (p = 0.28) and pond training (p = 0.33) did not significantly reduce post-stocking mortality. Early (125 mm total length) and late-stocked (receiving water was 2-4°C) tiger muskies showed no significant difference (p = 0.43) for decreasing post-stocking mortality when compared to normal-stocked (early October) tiger muskies in 1996. In 1997, an adjusted late (receiving water was 5-9°C) resulted in a decrease in post-stocking mortality when compared to normal stocking under similar conditions with predators (p = 0.02) and without predators (p = 0.10). The acceptability index is intended to assist in the allocation of limited juvenile tiger muskies. The index consists of five primary attributes which include temperature regime, water clarity, living and non-living cover, escapement potential, and availability of prey. These primary attributes are designed to assess the suitability of a water. The derived suitability rating is combined with an acceptability attribute score to obtain a likelihood for successfully establishing tiger muskies. With present knowledge, reservoirs with values of low-medium or low should not be stocked.
Keywords: aquaculture; fish production; aquatic sciences